Perlindungan Hukum Konsumen Muslim Atas Produk Pangan Tidak Bersertifikat Halal Di Kota Batam - Tommy Liusudarso; Junimart Girsang; Ampuan Situmeang (Pascasarjana Ilmu Hukum, Universitas Widyagama Malang, 2022)
The city of Batam is a city with a population that is predominantly Muslim, where in ensuring every believer of religion to worship and carry out his religious teachings, In ensuring that all food products circulating in Batam City do not contain unlawful/not in accordance with Islamic law, the government has regulated in the laws and regulations, where products that enter, are circulated, and traded in the territory of Indonesia must be certified halal. To analyze the problem of legal protection for consumers for food products that are not certified halal, it can be analyzed with the Theory of Legal Protection from Philipus M. Hadjon. The objectives to be achieved in this study are: To analyze the legal protection of consumers for non-halal certified food products circulating in Batam City. From the results of the study, it can be seen that preventive and repressive legal protection for consumers for food products that are not halal certified has been accommodated in the Legislative Regulations, but the preventive efforts made by the government are still not optimal in this case the Halal Product Guarantee Agency (BPJPH). because there are still many non-halal food products circulating and being traded.